Particulate organic carbon export fluxes across the Seychelles-Chagos thermocline ridge in the western Indian Ocean using 234Th as a tracer - Seo, Junhyeong; Kim, Intae; Kang, Dong-Jin; Lee, Hyunmi; Choi, Jin Young; Ra, Kongtae; Rho, TaeKeun; Park, Kyungkyu; Kim, Suk Hyun (Frontiers in Marine Science, 2024)
We investigated the export flux of particulate organic carbon (POC) using 234Th as a tracer in the western Indian Ocean along 60°E and 67°E transects in 2017 and 2018. The Seychelles-Chagos Thermocline Ridge (SCTR), where production is relatively high due to nutrient replenishment by upwelling of subsurface water, was observed at 3°S – 12°S in 2017 and 4°S – 13°S both 60°E and 67°E in 2018. POC fluxes in 2017 showed no differences between the SCTR and non-SCTR regions. However, in 2018, the POC fluxes in the SCTR regions (8.52 ± 7.89 mmol C m–2 d–1) were one order of magnitude higher than those observed in the non-SCTR regions (0.63 ± 0.07 mmol C m–2 d–1), which appeared to be related to the strong upwelling of subsurface water. These POC fluxes were comparable to those observed under bloom conditions, and thus, are important for estimating the efficiency of carbon sequestration in the ocean.